Voices from Rural Thailand: Understanding the Root Causes of Adolescent Pregnancy - Panjarut, Laisuwannachart; Chamroonsawasdi , Kanittha; Vatanasomboon , Paranee; Kittipichai , Wirin (YCAB Publisher, 2024)
Background: Adolescent pregnancy is an important global health concern. Almost 21 million adolescent women between the ages of 15 and 19 in developing countries become pregnant, and approximately 12 million of them give birth annually. Adolescent pregnancy has consequences for the health, social, and economic outcomes of adolescent women, their babies, and their families. Those in rural areas are particularly vulnerable due to poverty, inadequate education, limited access to contraception, and traditional beliefs. Objective:This qualitative study aims to explore the root causes of adolescent pregnancy in rural Thailand. Methods: This qualitative study was conducted from August to September 2023. We collected data through in-depth interviews with three mother-daughter dyads, whose daughters experienced adolescent pregnancy, and focus group discussions among four healthcare providers and four school teachers. We transcribed the data verbatim and applied thematic analysis. Results: The findings showed that the root causes of adolescent pregnancy include: 1) inadequate problem-solving skills to prevent adolescent pregnancy; 2) ineffective sexual communication; 3) poor family relationships; and 4) poor behavior control to prevent adolescent pregnancy. Conclusion:Our findings reveal the root causes of adolescent pregnancy in rural Thailand. Understanding these factors allows us to better address the unique challenges faced by adolescents in these communities. We should focus on these factors to design tailored interventions and involve multilevel stakeholders, including family, school, and healthcare services to prevent adolescent pregnancy. Keywords: Adolescent pregnancy; family functioning; mother-daughter dyads; The root causes; Thailand